‘Language Debates’ in Interwar Kaunas: Hebraists vs. Yiddishists - Andriejauskienė, Julijana (Lietuvos istorijos studijos, 2024)
The rise of the modern Jewish culture and national consciousness among East European Jews increased the relevance of the question of the ‘national’ language. The phenomenon, called riv ha-leshonot in Hebrew and shpraknkampf in Yiddish, emerged, meaning the war of the languages. More or less all centres of the East European Jewish community were affected by the phenomenon of this ‘conflict’. Kaunas Jewry was not an exception in this struggle. The article looks closely at the linguistic debates of Kaunas City Jews in the Republic of Lithuania (1918–1940). This research presents the linguistic preferences of Kaunas Yiddishists and Hebraists, and highlights how this contradiction manifested itself in the different spheres of the Jewish life, especially in education.
Keywords: Jews; Kaunas; ‘language battle’; interwar; Yiddishists; Hebraists